1990
DOI: 10.1079/bjn19900078
|View full text |Cite
|
Sign up to set email alerts
|

Effect of defaunation on protein and fibre digestion in sheep fed on ammonia-treated straw-based diets with or without maize

Abstract: Using a defaunating method which preserved bacteria and fungi in the rumen, the effect of protozoa on protein and fibre digestion was studied in six adult wethers in relation to the nature of the diet. Sheep were given daily, 42 g dry matter (DM)/kg metabolic body-weight (WO"), one of two isonitrogenous diets: one contained ammonia-treated wheat straw as the only energy source (diet S) and the other was supplemented with maize grain pellets (diet SM). Mean daily intakes (g/d) of nitrogen, neutral-detergent fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…Indeed, in our study, defaunation decreased in sacco DM degradation, but similar results have been observed by other authors [18,36]. The decrease of the in sacco DM degradation could be explained on the one hand, by the decrease in enzymatic activities and on the other hand, by the modification of the structure of the microbial population, after defaunation.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, in our study, defaunation decreased in sacco DM degradation, but similar results have been observed by other authors [18,36]. The decrease of the in sacco DM degradation could be explained on the one hand, by the decrease in enzymatic activities and on the other hand, by the modification of the structure of the microbial population, after defaunation.…”
Section: Discussionsupporting
confidence: 74%
“…In such conditions, defaunation decreases bacterial N recycling and OM digestibility (Eugène et al, 2004b) while increasing the efficiency of microbial protein synthesis (EMPS; Ushida et al, 1990). In such conditions, defaunation decreases bacterial N recycling and OM digestibility (Eugène et al, 2004b) while increasing the efficiency of microbial protein synthesis (EMPS; Ushida et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…While the bacteria are the most numerous cellulolytic organisms in the rumen, some protozoal species are also believed to produce plant cell wall hydrolases and their larger individual size means that they could account for a significant proportion of rumen fibre digestion [4]. Defaunation, the removal of protozoa from the rumen, results in depressed plant fibre breakdown under conditions where nitrogen is not limiting, again suggesting a significant role for the protozoa in ruminal fibre digestion [5].…”
Section: Introductionmentioning
confidence: 99%